Aerated Blast-Furnace-Slag Filters for the Simultaneous Removal of Nitrogen and Phosphorus from Primary Facultative Pond Effluents - Hamdan, Rafidah; Mara, Duncan (International Journal of Integrated Engineering, 2013)
Abstract: Rock filters (RF) are a promising alternative natural wastewater treatment technology for upgrading waste stabilization pond (WSP) effluents.  However, the use of RF to remove nutrients, such as nitrogen (N) and phosphorus (P), is very limited. Therefore, the present study was carried out to investigate the performance of aerated RF (ARF) systems for removing both nitrogen and phosphorus from domestic wastewater using blast furnace slag (BFS) as the filter medium. The performance of two aerated BFS filter systems, a horizontal-flow ARF and a vertical upflow ARF, was compared: for N and P removals. A further aim of the study was to determine if either or both of these BFS-ARF systems could produce effluents which complied with the nutrient removal requirements of the EU Urban Waste Water Treatment Directive (UWWTD) (91/271/EEC) for small communities. From the results of the present study it can be concluded that the both BFS-ARF are suitable unit processes for removing N and P from primary facultative pond effluents. The vertical-upflow BFS-ARF has the advantage of removing more ammonium-N (to below 1 mg N/L), but the disadvantage of removing less total-N. Further research on optimizing the design and performance of both BFS-ARF is warranted, and their performance in warm-climate countries requires to be investigated.